Opposite Trends in the Regulation of Pornography? Policy Differentiation and Policy Convergence Across 26 Countries Between 1960 and 2010. Issue 7 (1st September 2016) - Person, Christian; Hurka, Steffen; Knill, Christoph
Abstract : In recent decades, the regulation of pornography has been confronted with challenges emerging from cultural change, economic interests, and technological progress. As a result, the respective regulatory frameworks have changed substantially in many countries. These changes have been accompanied by fierce political struggles and societal value conflicts. However, there are few comparative studies on the reactions of national governments to these problems. In this article, we present new empirical data on the regulation of pornography in 26 countries between 1960 and 2010. To assess regulatory change, we rely on a new measurement approach that considers the extent to which governments intervene into individual freedoms and the degree to which noncompliance with these rules is actually sanctioned. Our analysis reveals a trend toward more permissive styles of pornography regulation. However, this trend is accompanied by growing regulatory specialization and a convergence toward more interventionist regimes for special types of pornography.